Social Studies Teaching in Preschool Education Period: A Document Review - Derya Ekiz Günal; Eyup Yünkül (Educational Academic Research)
In this study, the research on social studies education in preschool education between 1999 and 2022 was analyzed in detail. A total of 70 studies were examined through YÖK National Thesis Center, ERIC, ULAKBİM, Google Scholar and Turcademy databases. The focal points of the research include sub-problems such as publication year, publication type, subject areas, method, design, study group, data collection tool, stated conclusion and recommendation. Descriptive analysis method was used to analyze the data obtained from the study, which was based on document analysis, one of the qualitative research methods. As a result of the research, it was determined that the majority of the studies examined were carried out in order to reveal the importance and place of teaching social studies and the disciplines within the scope of this course. In addition, it was determined that there has been an increase in the number of studies conducted in the field since 2012 and the most studies were conducted in 2019. Finally, other important findings were that most of the studies in the field were carried out in the form of articles, most of the studies focused on the subject area of geography and were generally conducted with a qualitative research approach.